Empirical Evidence on the Effects of Environmental Policy Stringency on Productivity Growth - Albrizio, Silvia (OECD Economics Department Working Papers, 2014)
This paper investigates the impact of changes in the stringency of environmental policies on productivity growth in OECD countries. Using a new environmental policy stringency (EPS) index, it estimates a reduced-form model of multi-factor productivity growth, where the effect of countries' environmental policies varies with pollution intensity of the industry and technological advancement. A multi-layer analysis provides insights at the aggregate economy, the industry and the firm level. At the aggregate economy level, a negative effect on productivity growth is found one year ahead of the policy change. This negative "announcement effect" is offset within three years after the implementation. At the industry level, a tightening of environmental policy is associated with a short-term increase in industry-level productivity growth, for the most technologically advanced country-industry pairs. This effect diminishes with the distance to the global productivity frontier, becoming insignificant at larger distances. At the firm level, only the technologically most advanced firms show a positive effect on productivity growth from a tightening of environmental policies, while a third of firms, the less productive ones, experience a productivity slowdown